Narsisme dan Implikasinya terhadap Gangguan Kepribadian Narsistik Perspektif Al-Qur’an - Saidah -; Afidatur Rohmah (Institut Agama Islam Negeri (IAIN) Keiri, 2021)
Humans should not love themselves too much, so that eventually they only care about themselves and tend to underestimate others. If such symptoms appear in the individual then he has a strong nature of narcissism. Having a strong narcissistic nature can trigger the emergence of a narcissistic personality which is included in personality disorders. The purpose of this study was to find verses related to narcissism and its implications for narcissistic personality disorder from the perspective of the Koran. This research includes library research which was carried out by searching for and collecting data according to the theme using primary data sources in the form of the Qur'an, and secondary data sources in the form of books, theses and journal articles related to narcissism. The method used is contextual maudū’i and the research results was presented in an analytical descriptive manner. The results of the research from this thesis are: (1) The meaning of narcissism in the Qur'an has at least two meanings: narcissism which is classified as a major sin and narcissism which is classified as a minor sin. (2) The implications of narcissism in the Koran for Narcissistic Personality Disorder (NPD) events are more directed to the second understanding, namely minor sins, which in this case are represented by the terms arrogance and terrn which have meaning, namely: fakhr, ḥasad, riyā', 'ujub, and 'utuw.